DISHARMONI PENANGANAN PERKARA TINDAK PIDANA PENCURIAN RINGAN - Albert Gregorius (2024)
Petty theft, regulated by Article 364 of the Indonesian Criminal Code (KUHP), constitutes one of the criminal acts posing challenges in its handling process. The problematic aspects related to resolving cases of petty theft involve legal dimensions, law enforcement policies, legal structures, and legal cultures. The primary objective of this research is to conduct a comprehensive analysis of legal issues emerging in the resolution of petty theft crimes and to strive for the optimization of the resolution process. In addressing this issue, three methodological approaches are employed: statutory approach, case approach, and conceptual approach. Research findings indicate an overlap in the handling of petty theft cases and uncertainty regarding the application of restorative justice in resolving such cases, highlighting the necessity for legal optimization in handling cases of petty theft crimes.